Microstructure and Mechanical Properties of Mg–RE–TM Cast Alloys Containing Long Period Stacking Ordered Phases: A Review - Liu, Huan; Huang, He; Sun, Jia-Peng; Wang, Ce; Bai, Jing; Ma, Ai-Bin; Chen, Xian-Hua (Acta metallurgica sinica : English letters, 2019)
Casting magnesium alloys hold the greatest share of magnesium application products due to their short processing period, low cost and near net shape forming. Compared with conventional commercial magnesium alloys or other Mg–RE-based alloys, the novel Mg–RE–TM cast alloys with long period stacking ordered (LPSO) phases usually possess a higher strength and are promising candidates for aluminum alloy applications. Up to now, two ways: alloying design and casting process control (including subsequent heat treatments), have been predominantly employed to further improve the mechanical properties of these alloys. Alloying with other elements or ceramic particles could alter the solidification pattern of alloys, change the morphology of LPSO phases and refine the microstructures. Different casting techniques (conventional casting, rapidly solidification, directional solidification, etc.) introduce various microstructure characteristics, such as dendritic structure, nanocrystalline, metastable phase, anisotropy. Further heat treatments could activate the transformation of various LPSO structures and precipitation of diverse precipitates. All these evolutions exert great impacts on the mechanical properties of the LPSO-containing alloys. However, the underlying mechanisms still remain a subject of debate. Therefore, this review mainly provides the state of the art of the casting magnesium alloys research and the accompanying challenges and summarizes some topics that merit future investigation for developing high-performance Mg–RE–TM cast alloys.